Faith Fleur by CTYMARY/ Muhammad Anas Zamzuri ... [et al.] - Zamzuri, Muhammad Anas; Md Juhari, Farah Najiha; Zainal, Rohzaiana; Saat, Fatin Syahirah (2021)
Faith Fleur is a local hair care product. The products produces include shampoo, serum, conditioners and more. This product can help users in dealing with hair problems such as damaged hair, dry hair and so on. This product company was established in 2017 and is located in Malaysia, namely in Selangor and Sarawak. Faith Fleur has a product name that is from the French word has made the name of this product interesting and unique. In addition, Faith Fleur is a halal product that does not contain chemicals and is safe for consumers to use and has a sales target group of M40 and above. Faith Fleur only focuses on producing hair care products, however Faith Fleur has a variety of hair care product and has made products that can be comparable to foreign products. Also, Faith Fleur has operational strategies that can help grow their business, including promoting products on specific days of celebration. Besides that, Faith Fleur products are not sold in stores but only done through agents, dropship and online and promote through social media platforms. Also, collaboration with influential people in the country or experienced models to promote this product will be able to further enhance this product. Custom in sales, there will definitely be rivals and Faith Fleur is no exception. There is fierce competition between other local products as well as international products. However, every business must have a well-managed cash flow. Finance should be one of the main component like in planning and managing the company's capital balance. Also, in business, there will definitely be rules and laws respectively but if employees break the rules, the business will take legal action against employees who break the rules. Besides that, focus on caring for customer’s feedback is the strategy of maintaining the company reputation. So, the company will make improvements to the feedback received.